Algorithm For Supporting Management Decision-Making On The Placement Of The Positions Of The Trunk Operators When Extinguishing Fires In The Tanks Of Vietnam - Nguyen The Tai, Denisov A.N., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the article, based on the analysis of data in open literature sources, it was concluded that in the USSR, in the period 1950-1990, there were at least 10 tank fires per year, in the world - 8, 2000-2020 in Russia - at least 5 fires in year, in Vietnam 1950-1990 - not less than 0,85 fires per year. And it is noted that since 2007, there have been no fires at the facilities of the oil refining complex in Vietnam. An algorithm is presented that allows you to select options for the location of personnel positions, for supplying a fire extinguishing agent for extinguishing a fire (by mixing) in tanks (in the absence of a roof) and for cooling the walls of burning and adjacent to the burning tanks. Using this algorithm, an analysis was carried out of the possible locations of the positions of the barrels in the tank farms of the Vietnamese oil refineries "Dung Quat" and "Ngi Son" for extinguishing and cooling the tanks during their burning.